Does the Public Sector HRM System Strengthen Staff Performance? - Manning, Nick; Watkins, Joanna; Degnarain, Nishan (World Bank, Washington, DC, 2016)
An important objective of any Human Resource Management (HRM) system in Government is to motivate staff to perform well. This GET note looks at several HRM levers that Governments have at their disposal to influence staff performance. In particular, some of the most common levers in the public sector include: effective recruitment and retention of staff; strong staff engagement in the organization’s mission; well-designed incentives for staff to perform as well as ‘opportunities to perform’; tailored training and capacity building; and high quality performance dialogues with staff and effective follow up. In designing a HRM system that utilizes these levers effectively, this GET Note shows that it is more important to diagnose the root cause and understand the major issues of poor performance, before proposing reform actions. This paper proposes three important design questions for managers of HRM systems to assess whether they have a well-designed HRM system. 1) Does the HRM system provide both ‘external incentives’ and ‘opportunities to perform’? Does the HRM system provide the right balance between short and long term incentives? And are the broader, supporting aspects of the HRM system working effectively? The note concludes by highlighting that even where the HRM system is well designed, careful consideration must be given to two further aspects: a) how to implement reforms to improve the design of the HRM system, and b) how to ensure that a well-designed HRM system is operating effectively.